KUALITAS E-MODUL PENULISAN KARYA ILMIAH BERBASIS QR-CODE SEBAGAI ALTERNATIF STUDI FORM HOME PADA MASA PANDEMI - Dina Fitria Handayani (Universitas Batanghari, 2022)
This research aims to test and describe the quality of QR code-based e-module on learning scientific writing. This research is an R&D with a 4D Model in the 3rd stage, namely the development stage. Data collection is done by using questionnaire and validation instruments. The e-module that have been prepared are tested for validity, practicality, and effectiveness. The results showed that the validation results obtained an average of 87.5% with very valid categories. Meanwhile, practicality tests from the aspect of use by lecturers obtained 93% results with very practical categories. In addition, the aspect of student response reviewed from the ease of use and time used obtained 81% with very practical categories. E-module is designed to be effective to improve students learning outcomes in writing scientific papers. In general, they are fall into very well category